Biomotor ecosystem model in futsal performance: correlational analysis of flexibility, speed, and body mass index on futsal player agility - Deni Mudian; Arif Fajar Prasetiyo (Universitas Suryakancana, 2026)
Futsal requires players to have good physical abilities, especially agility to change direction quickly and precisely during the match. Agility is influenced by several biomotor components, such as flexibility, speed, and body composition, which can be measured through Body Mass Index (BMI). This study aims to analyze the relationship between flexibility, speed, and Body Mass Index (BMI) on the agility of futsal players. The study used a quantitative approach with a correlational design. The research sample consisted of 30 players who are members of the Futsal Student Activity Unit (UKM) at Subang University and were selected using a purposive sampling technique. Data collection was carried out through a sit and reach test to measure flexibility, a sprint test to measure speed, height and weight measurements to calculate BMI, and the Illinois Agility Test to measure agility. Data were analyzed using descriptive statistics and Pearson Product Moment correlation. The results showed that speed had the strongest relationship with agility (r = 0.58), followed by flexibility (r = 0.42) and Body Mass Index (r = 0.36). These findings indicate that futsal player agility is influenced by several interrelated biomotor components. Therefore, training programs need to address speed, flexibility, and body composition to improve futsal player performance